(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article gives information about the process of “idiomaticization” lies in diachronic evolution, idiomaticity cannot be adequately explained by the generative rules. Neither a given sense or a given syntactic structure by itself constitutes an idiom. Rather it is the regular association of one with the other that is the source of idiomaticity